2022
DOI: 10.3390/pathogens11091009
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Noncoding RNAs in Bovine Mastitis Diseases

Abstract: Non-coding RNAs (ncRNAs) are an abundant class of RNA with varying nucleotide lengths. They have been shown to have great potential in eutherians/human disease diagnosis and treatments and are now gaining more importance for the improvement of diseases in livestock. To date, thousands of ncRNAs have been discovered in the bovine genome and the continuous advancement in deep sequencing technologies and various bioinformatics tools has enabled the elucidation of their roles in bovine health. Among farm animals’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 177 publications
0
7
0
Order By: Relevance
“…Alternative methods of diagnosing mastitis in dairy cattle are thus needed. MicroRNA has recently been recognised as a potential diagnostic tool in the detection of bovine mastitis ( 24 ). Although many studies of miRNA expression levels in bovine milk have been carried out, most of them have evaluated mastitis status using CMTs, whereas our study employed both CMTs and SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative methods of diagnosing mastitis in dairy cattle are thus needed. MicroRNA has recently been recognised as a potential diagnostic tool in the detection of bovine mastitis ( 24 ). Although many studies of miRNA expression levels in bovine milk have been carried out, most of them have evaluated mastitis status using CMTs, whereas our study employed both CMTs and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs encapsulated in vesicles or conjugated to RNA-binding lipoproteins are more stable and can be measured by a range of techniques, including quantitative PCR, digital PCR and high-throughput assays ( 25 ). A number of studies have identified miRNAs associated with mastitis in cattle ( 18 , 19 , 34 , 37 ); however, different miRNAs have been proposed as mastitis biomarkers in different studies ( 24 ). The low repeatability of the results supporting certain miRNAs as viable biomarkers may be associated with the type of microorganism responsible for infection.…”
Section: Introductionmentioning
confidence: 99%
“…Between them, mir-6525 and mir-669 were reported in a review on the role of non-coding RNAs in bovine mastitis diseases as dysregulated miRNAs during mastitis infection by Staphylococcus aureus and Streptococcus agalactiae, respectively 18 . Mir-149, as shown in our integrated network (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs, untranslated RNA molecules that play a regulatory role in gene expression, are involved in many biological processes. These functional RNA molecules are divided into several groups such as small interfering RNA (siRNA), small nucleolar RNA (snoRNA), circular RNAs (circRNAs), PIWI-interacting RNA (piRNA), microRNA (miRNA), and long non-coding RNA (lncRNA) 18 . Among these, miRNAs and lncRNAs have attracted the attention of researchers in the field of immune-related gene expression signatures 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In this pilot study, we selected some inflammation-related miRNAs, among the most abundant found in cow milk, which are hsa-miR-21-5p , hsa-miR-29b-3p , and hsa-miR-148a-3p . Hsa-miR-148a-3p is involved in chronic inflammatory and autoimmune diseases, hsa-miR-21-5p regulates the expression of proinflammatory protein PDCD4 upon lipopolysaccharide (LPS) stimulation, while hsa-miR-29b-3p is repressed by the NF-κB pathway and can repress TNFAIP3, a negative regulator of NF-κB pathway and changes in their expression in the case of mastitis have been reported. For the lipid profile, we investigated the levels of saturated FAs, unsaturated FAs, and their ratios. The total antioxidant activity of milk was measured with the oxygen radical absorbance capacity (ORAC) assay and was used as a measure of milk antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%